2023
DOI: 10.3389/fonc.2023.1088038
|View full text |Cite
|
Sign up to set email alerts
|

Cancel cancer: The immunotherapeutic potential of CD200/CD200R blockade

Abstract: Immune checkpoint molecules function to inhibit and regulate immune response pathways to prevent hyperactive immune activity from damaging healthy tissues. In cancer patients, targeting these key molecules may serve as a valuable therapeutic mechanism to bolster immune function and restore the body’s natural defenses against tumors. CD200, an immune checkpoint molecule, is a surface glycoprotein that is widely but not ubiquitously expressed throughout the body. By interacting with its inhibitory receptor CD200… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 89 publications
0
7
0
Order By: Relevance
“…Using a cytokine/chemokine array, we detected an elevated level of IFNβ in 2208L tumors treated with IACS-70654 as compared to controls treated with vehicle ( Figure 5E ). IACS-70654 also downregulated genes involved in the regulation of inflammation and inhibition of cytokine production, such as Cd200 and Cebpb which have been shown to induce immunosuppression in the TIME (Choe and Choi, 2023, Matherne et al, 2023) ( Figure 5A and Supplemental S5C). In tumor cells, these results showed that in 2208L tumor cells IACS-70654 induced both MHCI expression and an IFN response, suggesting induced antigen presentation and immune stimulation including T-cell activation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Using a cytokine/chemokine array, we detected an elevated level of IFNβ in 2208L tumors treated with IACS-70654 as compared to controls treated with vehicle ( Figure 5E ). IACS-70654 also downregulated genes involved in the regulation of inflammation and inhibition of cytokine production, such as Cd200 and Cebpb which have been shown to induce immunosuppression in the TIME (Choe and Choi, 2023, Matherne et al, 2023) ( Figure 5A and Supplemental S5C). In tumor cells, these results showed that in 2208L tumor cells IACS-70654 induced both MHCI expression and an IFN response, suggesting induced antigen presentation and immune stimulation including T-cell activation.…”
Section: Resultsmentioning
confidence: 99%
“…Using a cytokine/chemokine array, we detected an elevated level of IFNβ in 2208L tumors treated with IACS-70654 as compared to controls treated with vehicle (Figure 5E). IACS-70654 also downregulated genes involved in the regulation of inflammation and inhibition of cytokine production, such as Cd200 and Cebpb which have been shown to induce immunosuppression in the TIME (Choe andChoi, 2023, Matherne et al, 2023) (Figure 5A and Supplemental S5C).…”
Section: Iacs-70654 Induced Both An Ifn Response and Antigen Presenta...mentioning
confidence: 95%
“…Likewise, mice lacking CD200 have an exaggerated response to influenza infection, leading to slower resolution of infection and greater lung damage ( 25 ). Interestingly, several viruses have evolved to express CD200-like proteins on the surface of infected cells, which interact with CD200R and inhibit killing ( 41 ). Thus, it is not unexpected that the CD200/CD200R axis might play an important role in modulating TB immunopathology.…”
Section: Discussionmentioning
confidence: 99%
“…CD200 is highly expressed on tumor cells, impairs antitumor immune responses, and is associated with poor prognosis. Although the blockade of CD200 has been shown to promote antitumor immunity, definitive clinical trial data on efficacy is still lacking ( 41 ). If CD200/CD200R blocking agents proceed to further clinical trials, however, it will be important to look for early signals of TB reactivation.…”
Section: Discussionmentioning
confidence: 99%
“…Both Tregs and MDSCs exert immunosuppressive effects in immunological responses to cancers and other diseases through various pathways and mechanisms ( 57 , 58 ). MDSCs express Arg-1 and iNOS, produce ROS, and downregulate anti-tumor immune activity via the release of different chemicals and factors in vivo ( 59 61 ). Local irradiation of tumor lesions could increase the production of chemokine ligand (CCL)2 and CCL5, which are associated with the recruitment of Tregs and monocytes ( 62 , 63 ).…”
Section: Immunosuppressive Effect Of Radiation Therapymentioning
confidence: 99%